Exploring young people's perceived climate change competence - Taurinen, Janina; Vilhunen, Elisa; Vesterinen, Veli-Matti; Veijonaho, Salla; Aeijaelae, Mikko; Ruuskanen, Taina (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
The climate change knowledge of young people is frequently assessed in research, but their perceived level of competence is seldom considered. We approached this research gap by exploring young people's perceptions on their climate change competence in terms of coping with and adapting to climate change. We collected 349 responses from a large Finnish scouting event in summer 2022 with a 20-item climate change competence perceptions questionnaire. We explored the results with two approaches: variable-oriented and person-oriented. We identified four key (competency) dimensions underlying the items, called Systems and science, Values and attitudes, Leadership and action, and Well-being. The person-oriented approach with a latent profile analysis revealed four distinct profiles called the Competent, the Climate-aware, the Science-oriented, and the Puzzled. The questionnaire could be further developed into a valuable instrument for understanding young people's perceptions and complemented with knowledge-based scales in evaluating the effectiveness of climate change education.